WRITTEN FIRST AID INFORMATION FOR PATIENTS IN THE EMERGENCY DEPARTMENT: A CLUSTER RANDOMISED CONTROLLED TRIAL. Issue 12 (23rd November 2015) - Pallot, D; O'Keeffe, C; Dawson, J; Mason, S; Oliver, E; Mulligan, J
Abstract : Objectives & Background: Patients with minor injuries create a significant workload for Emergency Departments. Each attendance is also an opportunity to deliver health education, and written information is established to be effective. Appropriate first aid may reduce the workload of the Emergency Department, and reduce injury morbidity. It was hypothesised that giving patients written first aid information during an attendance will improve confidence and knowledge of first aid. Methods: The study was run at the Northern General Hospital, Sheffield, from 15th March to 4th April 2014. Consecutive adult patients attending the ED with eligible presenting complaints between 9am and 8pm were recruited. Patients were selected from those assigned to the minor injuries area of the ED. The eligible presenting complaints were: – Limb injuries – Wounds – Head injuries Allocation to intervention and control groups was done by day of presentation based on a computer generated random sequence. Patients in the intervention arm were given written information about first aid produced by the British Red Cross. Both arms also received usual care inlcuding any normal verbal advice and other written information. The initial questionnaire was given to consenting patients in both groups before being seen by a doctor, and before the written information was given in the intervention group. The ED records were used to collect diagnosis and demographic data. Follow up questionnaire was performed at 4 weeks. Re-attendance data was collected from ED records at 3 months. Analysis of confidence was by repeated measures ANOVA and knowledge of individual treatments by binary logistic regression. Results: 293 patients completed the initial questionnaire and 194 (66%) were followed up. There was no effect on confidence in performing first aid on themselves (mean effect 0.321 on a scale of 0 to 10, 95% confidence −0.335 to 0.978). The intervention improved knowledge of limb injuries (p=0.006) and wounds (p=0.032) but not head injuries. The intervention also reduced suggestions to seek medical assistance in the intervention group (p<0.001). Conclusion: Written information improves knowledge, but does not affect confidence in first aid management of minor injuries. The follow up period was too short to show a change in attendance behaviour and further work should analyse the effect of first aid written information on patient behaviour.